The smallest snowman - Fisch, Sarah; Durk, Jim (New York : Scholastic Inc., 2006)
Who will win the biggest snowman contest? Could it be Clifford the tiny red puppy?
Keywords: Clifford (Fictitious character from Bridwell) -- Juvenile fiction; Snowmen -- Juvenile fiction; Contests -- Juvenile fiction